Thrombin-stimulated Human Platelets Express Molecular Forms of α-Granule Factor V (FV), which Differ from FVa - Wyshock, Edward G; Stewart, Gwendolyn J; Colman, Robert W (Thrombosis and Haemostasis, 1994)
Binding of 125I-Fab fragments of chain-specific antibodies indicate that both heavy and light chains of a-granule factor Va (FVa) were externalized on the platelet membrane after stimulation with thrombin. Using a Mab against the activation peptide of factor V (FV), the epitope appears on the stimulated platelet surface. Half as much light chain and heavy chain (FVa) was expressed compared to the activation peptide, suggesting that expression of α-granule FV occurs after thrombin stimulation. Using an ELISA, we find that 32% of a-granule FV was released and 68% is retained in the platelet pellet. Immunoblots of platelets indicate that FV exists in 200 kDa und 150 kDa forms, representing incomplete cleavage, while the releasate demonstrates a more complete cleavage by proteases. We conclude that expression of α-granule FV is quantitatively greater than that released and exists in molecular forms which cannot be completely explained by the binding of FVa.